Proceedings of the 8th International Conference on Multimodal Interfaces 2006
DOI: 10.1145/1180995.1181017
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of visual-auditory and visual-tactile feedback on user performance

Abstract: In a meta-analysis of 43 studies, we examined the effects of multimodal feedback on user performance, comparing visualauditory and visual-tactile feedback to visual feedback alone. Results indicate that adding an additional modality to visual feedback improves performance overall. Both visual-auditory feedback and visual-tactile feedback provided advantages in reducing reaction times and improving performance scores, but were not effective in reducing error rates. Effects are moderated by task type, workload, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(130 citation statements)
references
References 33 publications
9
115
0
Order By: Relevance
“…A review of 43 such studies [10] indicated that combining visual feedback with auditory or tactile feedback led to reduced reaction times and improved performance measures, although error rates were not improved. Studies on the effects of haptic feedback in handheld touchscreen devices indicated improvements in subjective workload [11] and reduced task completion times [12]; in both of these cases, improvements were also observed in error rates.…”
Section: Touchscreens and Multimodal Interactionmentioning
confidence: 99%
“…A review of 43 such studies [10] indicated that combining visual feedback with auditory or tactile feedback led to reduced reaction times and improved performance measures, although error rates were not improved. Studies on the effects of haptic feedback in handheld touchscreen devices indicated improvements in subjective workload [11] and reduced task completion times [12]; in both of these cases, improvements were also observed in error rates.…”
Section: Touchscreens and Multimodal Interactionmentioning
confidence: 99%
“…Attending to multimodality, several studies (i.e. see meta-analysis performed in [8]) have reported the benefits of providing richer sensory outputs in a VE. But despite its benefits, multimodality can become an additional source of mismatches for the design of a VE, due to the synchronization requirements of all the system sensory outputs.…”
Section: Introductionmentioning
confidence: 99%
“…The approach stems from the multiple resource theory [93] that suggests that humans can efficiently compartmentalize information processing across modalities, although not entirely without interference [94].  Using this approach enables all relevant information for motor learning involving a motor task to be efficiently and simultaneously delivered to the user.…”
Section: Style 4: Concurrentmentioning
confidence: 99%